An evidence for an organic N-doped multiwall carbon nanotube heterostructure and its superior electrocatalytic properties for promising dye-sensitized solar cells. Issue 18 (9th April 2018) - Arbab, Alvira Ayoub; Memon, Anam Ali; Sahito, Iftikhar Ali; Mengal, Naveed; Sun, Kyung Chul; Ali, Mumtaz; Jeong, Sung Hoon
Abstract : Mechanism of synthesis of an organic N-doped MWCNT heterostructure for Pt-free DSSCs. Abstract : A novel organic heteroatom doping technique is proposed for the synthesis of N-doped multiwall carbon nanotube (MWCNT) heterostructures. The approach involves the effective doping of MWCNTs with nitrogen via a cationised bovine serum albumin (cBSA) protein complex. The cationization of BSA releases an exceptional number of activated nitrogen species present in localized amino groups, which are further embedded into the MWCNT framework. The amino groups present in BSA act as nitrogen donors and surface stabilizing agents to generate a highly conductive and functionalized carbon heterostructure. The doped nitrogen was present in the form of pyridinic and pyrrolic states, as evidenced by XPS analysis. Organic N-doped MWCNTs with predominant pyridinic N atoms displayed superior charge transfer ( R CT = 0.06 Ω) owing to their superior electrocatalytic activity. A DSSC fabricated with organic N-doped MWCNT heterostructures exhibited a high conversion efficiency of 9.55%, which was similar to that of a Pt cathode, with an efficiency of 9.89%. The superior electrochemical performance of organic N-doped MWCNT heterostructures is due to the high charge polarization arising from the difference in electronegativity between nitrogen and carbon as well as the structural strain caused by the cationic BSA protein complex. Our proposed system provides new routes for the synthesis of organic heteroatom-doped nanomaterials for promising energy storage devices.